PENGARUH PENGEMBANGAN KARIR, MOTIVASI KERJA, DISIPLIN KERJA, DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA KARYAWAN: Studi Pada Koperasi Simpan Pinjam Nasari Yogyakarta - Dila Damayanti; Muhammad Awal Satrio Nugroho; Shafira Salsabila (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2022)
Human resource is very important in a company. The reason for this examination is to examine the impact of profession improvement, work inspiration, work discipline, and authoritative obligation to worker execution. This exploration was led in Koperasi Simpan Pinjam Nasari Yogyakarta. This exploration utilizes a quantitative methodology. The quantity of tests utilized upwards of 32 workers, by the strategy for immersed examining (evaluation). The outcomes showed that the incomplete advancement of the Career and discipline makes a positive difference and critical on representative execution Koperasi Simpan Pinjam Nasari Yogyakarta. In the interim, motivation and Organizational Commitment significantly affects representative execution Koperasi Simpan Pinjam Nasari Yogyakarta. All the while Career development, Motivation, work discipline, and Organizational Commitment influence the Performance.